Iowa RBA, March 11-14, 1996 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1996)
Iowa RBA update for March 11-14, 1996. Highlights of the update include sightings of a White-winged Scoter, Glaucous Gull, Thayer's Gull, White-winged Crossbill and a Saw-whet Owl. Epson - sheet feed/flatbed